Calretinin Variant in Hirschsprung Disease: Pretransitional Sign and Surgical Planning - Muller, Cecile Olivia; Hobeika, Christian; Montalva, Louise; Berrebi, Dominique; Bonnard, Arnaud (European Journal of Pediatric Surgery, 2016)
Objectives Calretinin immunohistochemistry (IHC) with slight submucosal positivity (variant) has been reported in short forms of Hirschsprung disease (HD). The first aim of our study was to confirm this variant being a pretransitional sign. The second was to evaluate if its presence on suction rectal biopsy was reliable enough for surgical planning.Methods We performed a monocentric retrospective study of all rectosigmoid HD between 2009 and 2014. Suction rectal biopsy defined two groups of calretinin results: P− group with no staining and P+ group with slight positivity. P− group final resection specimen was retrospectively reanalyzed looking for the variant to appear within the aganglionic bowel. P+ group surgical management was analyzed in terms of initial symptoms, radiological results, type of surgery and outcome, before and after formal identification of the variant by our pathologists (2011).Results Overall, 54 patients with rectosigmoid HD were included from 2009 to 2014. In the P− group (48.2%), the variant pattern finally appeared on all surgical resection specimens, 1 cm before the transitional zone (minimum–maximum: 0–5 cm). In the P+ group, 46% of these patients had peroperative biopsies before the transanal pull through before 2011 against 10% after 2011, with 100% of ganglionic coloanal anastomosis and similar outcome.Conclusion We confirmed our hypothesis of this varied pattern of calretinin being a pretransitional sign only visible on rectal suction biopsies in short segment HD and reliable enough to plan direct transanal pull through.
Keywords: Hirschsprung disease; calretinin; transanal pull through